Preliminary Clinical Study of the Differences Between Interobserver Evaluation and Deep Convolutional Neural Network-Based Segmentation of Multiple Organs at Risk in CT Images of Lung Cancer - Zhu, Jinhan; Liu, Yimei; Zhang, Jun; Wang, Yixuan; Chen, Lixin (Frontiers in Oncology, 2019)
Background: In this study, publicly datasets with organs at risk (OAR) structures were used as reference data to compare the differences of several observers. Convolutional neural network (CNN)-based auto-contouring was also used in the analysis. We evaluated the variations among observers and the effect of CNN-based auto-contouring in clinical applications. Materials and methods: A total of 60 publicly available lung cancer CT with structures were used; 48 cases were used for training, and the other 12 cases were used for testing. The structures of the datasets were used as reference data. Three observers and a CNN-based program performed contouring for 12 testing cases, and the 3D dice similarity coefficient (DSC) and mean surface distance (MSD) were used to evaluate differences from the reference data. The three observers edited the CNN-based contours, and the results were compared to those of manual contouring. A value of P<0.05 was considered statistically significant. Results: Compared to the reference data, no statistically significant differences were observed for the DSCs and MSDs among the manual contouring performed by the three observers at the same institution for the heart, esophagus, spinal cord, and left and right lungs. The 95% confidence interval (CI) and P-values of the CNN-based auto-contouring results comparing to the manual results for the heart, esophagus, spinal cord, and left and right lungs were as follows: the DSCs were CNN vs A: 0.914~0.939(P=0.004), 0.746~0.808(P=0.002), 0.866~0.887(P=0.136), 0.952~0.966(P=0.158) and 0.960~0.972 (P=0.136); CNN vs B: 0.913~0.936 (P=0.002), 0.745~0.807 (P=0.005), 0.864~0.894 (P=0.239), 0.952~0.964 (P=0.308) and 0.959~0.971 (P=0.272); and CNN vs C: 0.912~0.933 (P=0.004), 0.748~0.804(P=0.002), 0.867~0.890 (P=0.530), 0.952~0.964 (P=0.308) and 0.958~0.970 (P=0.480), respectively. The P-values of MSDs are similar to DSCs. The P-values of heart and esophagus is smaller than 0.05. No significant differences were found between the edited CNN-based auto-contouring results and the manual results. Conclusion: For the spinal cord, both lungs, no statistically significant differences were found between CNN-based auto-contouring and manual contouring. Further modifications to contouring of the heart and esophagus are necessary. Overall, editing based on CNN-based auto-contouring can effectively shorten the contouring time without affecting the results. CNNs have considerable potential for automatic contouring applications.